99mTc-interleukin-2 scintigraphy in normal subjects and in patients with autoimmune thyroid diseases: a feasibility study. - Chianelli, M; Mather, S; Grossman, A; Sobnak, R; Fritzberg, A; Britton, K; Signore, A (2008)
PURPOSE: Radiolabelled interleukin-2 is a radiopharmaceutical used for the study of chronic inflammatory processes. (123)I-labelled interleukin-2 has successfully been used in a large number of patients affected by several immune-mediated diseases. (123)I, however, is expensive and not readily available. We have, therefore, developed a method for labelling interleukin-2 with (99m)Tc to high specific activity based on the use of an N(3)S bifunctional chelating agent. In this paper, we describe the results obtained with (99m)Tc-interleukin-2 in a series of eight normal subjects and of 12 patients with autoimmune thyroid diseases. METHODS: Biodistribution, pharmacokinetics, haematological and systemic toxicity, radiation absorbed dose and in vivo targeting were studied. RESULTS: Results showed rapid plasma clearance of (99m)Tc-interleukin-2 with retention mainly in the kidneys. Biodistribution and kinetics were similar to that observed for (123)I-interleukin-2. No acute systemic toxicity was found; a small decrease in peripheral blood lymphocytes was observed in the first hours only in patients, but it was mild and transient. (99m)Tc-interleukin-2 accumulated, to varying extents, in the thyroid of all patients affected by autoimmune thyroid diseases but not in the thyroid of normal subjects. The effective dose equivalent of a diagnostic activity of (99m)Tc-interleukin-2 (185 MBq) was 1.35 mSv. No correlation was observed between thyroid autoantibodies and uptake of (99m)Tc-interleukin-2. CONCLUSIONS: The use of (99m)Tc-interleukin-2 is safe and simple; the favourable dosimetry and biodistribution and the rapid clearance make it potentially useful for the study of chronic inflammatory diseases such as autoimmune thyroid disease.